Psychiatric comodorbidity in forensic psychiatry - Žarković-Palijan, Tija (Array, 2009)
For the past several years a numerous studies in the field of forensic psychiatry confirmed a close relationship between violent offenders and comorbid substance abuse. The comorbid substance abuse in violent offenders was usually unrecognized and misdiagnosed. Furthermore, comorbidity in forensic psychiatry describes the co-occurrence of two or more conditions or psychiatric disorder known in the literature as dual diagnosis and defined by World Health Organization (WHO). In fact, many violent offenders have multiple psychiatric diagnose. Today, the primary focus of forensic psychiatry treatment services (inpatient or community) is management of the violent offenders with psychiatric comorbidity which requires a multilevel, evidence based approach to the patient. Forensic treatment service effectiveness appears to be associated with individual case management and approach including psychotherapy, pharmacotherapy and occupational therapy in order to achieve optimal rehabilitation, prevention of recidivism and stability in social functioning of the patient in the community